Perancangan Tata Kelola Teknologi Informasi Menggunakan COBIT 2019 Pada Dinas Perpustakaan Dan Kearsipan Kota Salatiga - Arya Pradipta; Augie David Manuputty (APTIKOM SUMSEL, 2022)
Current technological developments play a very important role in organizations and companies, both profit and non-profit. Information technology has been widely implemented in organizations and companies to support or facilitate the activities of organizations and companies. With the development of information technology, the needs of organizations and companies in terms of governance are very important to achieve the vision and mission of the organization and company. The research was conducted using the COBIT 2019 framework for the design of information technology governance at the Salatiga City Library and Archives Service to be better in the future. Methods of collecting data by conducting interviews and observations to determine the current state of the organization at the Salatiga City Library and Archives Service in implementing the implementation of information technology. The approach and problem analysis were carried out to produce recommendations for the management of information technology at the Salatiga City Library and Archives Service. After conducting interviews and discussions with the Salatiga City Library and Archives Office, the incumbent wants the organization to be ready to face changes in the future. Which is related to one of the COBIT processes, namely BA105 Managed Organizational Change, this is very in line with the objectives of the office holders at the Salatiga City Library and Archives Service, which aims to assist organizations in preparing for changes that may occur in the future, especially in the field of information & technology. With this research report, it is hoped that it can be used as a reference or reference for the Salatiga City Library and Archives Service to help improve organizational performance and make information governance better.